2013
DOI: 10.1016/j.repc.2012.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve replacement combined with coronary artery bypass graft surgery in patients with moderate-to-severe ischemic mitral regurgitation

Abstract: CABG+MVR can be performed safely in patients with moderate-to-severe IMR. CABG+MVR resulted in lower rates of complications than CABG only. Both surgical approaches resulted in significant improvement of postoperative LVEF. However, there was greater improvement in the CABG+MVR group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
2
0
3
Order By: Relevance
“…However, they underwent other valves procedures on pulmonary or tricuspid valves less frequently than non-COPD patients. In this way, Sá et al [21] found that mitral valve replacement may be performed safely, concomitantly with CABG, in patients with moderate-to-severe ischemic mitral regurgitation. In such patients, the combined procedure resulted in lower rates of postoperative atrial fibrillation and low cardiac output than CABG only.…”
Section: Discussionmentioning
confidence: 99%
“…However, they underwent other valves procedures on pulmonary or tricuspid valves less frequently than non-COPD patients. In this way, Sá et al [21] found that mitral valve replacement may be performed safely, concomitantly with CABG, in patients with moderate-to-severe ischemic mitral regurgitation. In such patients, the combined procedure resulted in lower rates of postoperative atrial fibrillation and low cardiac output than CABG only.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that severe ischaemic heart disease usually presents with some degree of mitral regurgitation (MR) that may need concomitant mitral valve replacement (MVR) along with coronary revascularization. 1 In the same context, current guidelines recommend evaluation of coronary artery disease (CAD) and subsequent revascularization of clinically significant CAD in all patients undergoing MVR for primary MV disease (MVD). 2 , 3 While both uncorrected CAD and residual MR after isolated coronary revascularization have shown negative impacts on the perioperative and long-term outcomes of patients with mitral valve disease (MVD); combined procedure [MVR + coronary artery bypass graft (CABG)] is also not devoid of complications.…”
Section: Introductionmentioning
confidence: 99%
“…Para realizar esta afirmación, nos basamos en el hecho de que la presencia de regurgitación mitral tiende a incrementar el cálculo de la fracción de eyección, la cual es muy dependiente de la postcarga. (1,13,70,88,100,104,116,117,119,123,124,125,129,130,142,190,219,224) Una fracción de eyección del ventrículo izquierdo más alta, en el contexto de una sobrecarga aguda de volumen del ventrículo izquierdo secundaria a la presencia de regurgitación mitral que ocurre de manera temprana en el pág. 133 transcurso de un infarto agudo de miocardio, puede enmascarar la verdadera extensión del daño miocárdico.…”
Section: Pág 131unclassified
“…El aparato valvular mitral (1,140,145,209,241) está constituido por la pared auricular izquierda, los músculos papilares y las regiones de la pared ventricular sobre la que asientan el anillo valvular, las cuerdas tendinosas -que comunican ambos músculos papilares con los velos valvulares-los velos mitrales anterior y posterior, y dos comisurasmedial y lateral-donde confluyen los velos valvulares. El funcionamiento normal de la válvula mitral depende de una adecuada interacción entre todos estos elementos.…”
unclassified
See 1 more Smart Citation